BUNYEV(S): A LINGUISTIC FRONTIER TO BE? (Filološke studije, 2019)
The arguably blossoming field of borderlands studies has not produced a single theory of borders, offering instead a plethora of terms often denoting overlapping concepts. This is precisely why – first – a theory of frontiers, specifically linguistic frontiers, is only outlined and – second – applied to the concrete area of Serbia’s Autonomous Province of Vojvodina. Then a close analysis of the Vojvodina’s populace of Bunyevs is offered in an attempt to better understand the process of the emergence of a linguistic frontier